-3f=18.09

Simple and best practice solution for -3f=18.09 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3f=18.09 equation:



-3f=18.09
We move all terms to the left:
-3f-(18.09)=0
We add all the numbers together, and all the variables
-3f-18.09=0
We move all terms containing f to the left, all other terms to the right
-3f=18.09
f=18.09/-3
f=-6+0.09/3

See similar equations:

| -5(4x-2)=-110 | | x-36=104 | | -5x-4=76 | | 7x-2=-4x+64 | | v+3=0 | | 5m+10+15m=60 | | 56-4x=8+4x | | a-968=-550 | | (2.8+2x)/8=0.8 | | -2(3x+3)=-48 | | 28=2(-12-x) | | 7+16y=11;4 | | 738=p+454 | | v+3=-12 | | (-8)+x=-1 | | 7x4+1x=-1+13x+7 | | -5x+2=5(3-x) | | -5x(x+2)=-(-5x+1)-x | | 5a+9+6a=35 | | -7(-2+3x)=203 | | 3(x+6)=4(x-13) | | z/5+80=88 | | -4(2x+3)=-(6x-20) | | 28.24=6g+3.58 | | -7/8=-3/4x+1/3 | | X=32m2 | | 5x-1+7-13+6x-4=13 | | 6u−36=-42 | | 9+4n=15-n | | 2r-18=-2 | | 2x-7=137-2x | | h+5.7=-5.7 |

Equations solver categories